'Rotor free-wheeling' in impaired F1FO-ATPase induces congenital hypermetabolism. (February 2023) - Nesci, Salvatore; Romeo, Giovanni
Abstract: A de novo heterozygous variant in the catalytic subunit of mitochondrial F1 FO -ATPase has been recently discovered by Ganetzky et al. to be the main cause of an autosomal dominant syndrome of hypermetabolism associated with defective ATP production. We describe how the 'rotor free-wheeling' causes this F1 FO -ATPase dysfunction in primary congenital hypothyroidism.